Implementation of the Complete Systematic Land Registration Program at the Palopo City National Defense Agency - Syahiruddin Syah; Herman Saputra; Kasmad Kamal (PINISI Discretion Review, 2023)
This study aims to determine the implementation of Complete Systematic Land Registration (Indonesia: Pendaftaran Tanah Sistematis Lengkap/PTSL) at the Palopo City National Land Agency Office using a descriptive qualitative method where the data collection techniques used are interviews, observation and documentation related to the implementation of the PTSL Program. The data obtained is then analyzed using qualitative analysis techniques through the process of condensing data, presenting data, and drawing conclusions by reviewing all data supported by using the theory put forward by Van Meter and Van Horn (1975) there are 6 indicators that influence the success or failure of policy implementation These include, among others, policy standards and targets, policy resources, inter-organizational communication and enforcement activities, characteristics of implementing agencies, economic, social and political conditions and dispositions of executors. The results of the study show that of the 6 indicators used the implementation of PTSL in Palopo City is still not going well, this can be seen from policy resources related to financial costs that differ in each village, communication between the village administration and the BPN regarding community land certificate files which are not complete yet run efficiently and there are problems with social, economic and political conditions between the community and the kelurahan related to counseling that is not circulated by the BPN regarding implementation points according to the rules based on SKB 3 Minister Number 25 of 2017 so that the active role of the Palopo city government needed to overcome this.